Are stock returns a leading indicator for real macroeconomic developments? - Johann Burgstaller (Johannes Kepler University of Linz, Department of Economics, 2002)
I examine whether or not returns on stock markets are a leading indicator for real macroeconomic developments in Austria, Japan and the USA. Further I deal with the concept of stock market efficiency, the question whether or not information from real and financial sectors of the economy is consistently priced on stock markets. This would not be the case if past macroeconomic developments could be used to improve forecasts of subsequent stock returns. Time series models are used to investigate the respective long-run relations between stock prices and other macroeconomic variables as well as short-term dynamics. I conclude that none of the markets under study is efficient in the above-mentioned strict sense. Only U.S. stock returns lead private consumption and, rather weakly, retail sales growth.
Keywords: C32; E44; G14; G15; 330; Stock returns; stock market efficiency; leading indicators; macroeconomic variables; vector error correction models; Kapitalertrag; Aktienmarkt; Effizienzmarktthese; Zeitreihenanalyse; Japan; USA; Österreich; Makroökonomischer Einfluss